The effectiveness of whole brain teaching on students' engagement and self discipline in learning english - Badewi, Sarah Amjd (Kulliyyah of Education, International Islamic University Malaysia, 2016)
This study examined the effects of the Whole Brain Teaching (WBT) strategy on students' engagement and self-discipline, in learning English. This study sought to answer the following questions: (1) Does whole brain teaching have a statistically significant effect on students' engagement in learning the English language? And (2) Does whole brain teaching have a statistically significant effect on students' self-discipline in learning the English language? The subjects were 71 students from the Al-Amin Islamic School in Gombak, Malaysia. This research is a quasi experimental design. The treatment, Whole Brain Teaching, was administered over a period of two weeks. The 71 students have been divided to two groups, 36 in the control group and 35 in the experimental group. The control group received their English lessons via the traditional method, while the experimental group received their English lesson via WBT. The instrument used was a questionnaire that was administered twice as a pretest and post- test. A paired-sample t-test was run on the data to establish the effects of the WBT, results were effective for the experimental group as scores were different score from the pretest. Therefore the WBT treatment did have an effect on student engagement and self-discipline, in learning English. It is suggested that teachers use this method.